2009
DOI: 10.1002/elan.200804552
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer‐Based Label‐Free Immunosensors Using Carbon Nanotube Field‐Effect Transistors

Abstract: Aptamer-based label-free immunosensors were fabricated for immunoglobulin E (IgE) detection using carbon nanotube field-effect transistors (CNTFETs). Aptamers are artificial oligonucleotides and thus are smaller than the Debye length. After aptamers were covalently immobilized on CNT channels, the electrical properties of the CNTFETs were monitored in real time. Introduction of IgE at various concentrations caused a sharp decrease in the source-drain current and gradual saturation at lower currents. From the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 54 publications
8
83
0
2
Order By: Relevance
“…The Langmuir adsorption isotherm fitted the experimental results well, as shown in Figure 10 (red dashed line). The K d was estimated to be 1.5 × 10 −8 M, which was comparable with the values obtained for Si nanowire (Cui et al, 2001) and CNT-FET biosensors (Abe et al, 2008;Maehashi et al, 2009) using antibody-antigen interactions, despite the fact that BSA molecules were considered to be directly adsorbed onto the graphene surface in this work rather than through a protein-protein interaction. Further experiments are needed to confirm the suitability of the Langmuir adsorption isotherm for these experimental results.…”
Section: Detection Of Protein Adsorptionsupporting
confidence: 85%
“…The Langmuir adsorption isotherm fitted the experimental results well, as shown in Figure 10 (red dashed line). The K d was estimated to be 1.5 × 10 −8 M, which was comparable with the values obtained for Si nanowire (Cui et al, 2001) and CNT-FET biosensors (Abe et al, 2008;Maehashi et al, 2009) using antibody-antigen interactions, despite the fact that BSA molecules were considered to be directly adsorbed onto the graphene surface in this work rather than through a protein-protein interaction. Further experiments are needed to confirm the suitability of the Langmuir adsorption isotherm for these experimental results.…”
Section: Detection Of Protein Adsorptionsupporting
confidence: 85%
“…Recently, various FET-based immunosensors using aptamers immobilized on nanomaterial sensing channels were reported [135][136][137][138][139][140][141][142][143]. For instance, So et al firstly demonstrated a FET biosensor based on SWCNT using aptamers as bioreceptors.…”
Section: Aptamers Instead Of Antibodiesmentioning
confidence: 99%
“…The SWCNT-FET sensor presented a conductance decrease upon aptamer-target binding, being able to detect thrombin, a coagulation protein, with a LOD of 10 ng·mL −1 [140]. Maehashi et al fabricated a SWCNT-FET immunosensor for immunoglobulin E (IgE) detection [137]. IgE is a protein overexpressed by individuals with immune deficiency diseases.…”
Section: Aptamers Instead Of Antibodiesmentioning
confidence: 99%
“…(9)(10)(11) Biomolecules such as DNA and proteins were detected using CNTFETs. (12)(13)(14)(15)(16)(17)(18) CNTs are also reported to have a higher ability to promote electron transfer reactions than conventional metal electrodes for electrochemical measurements. (19) When CNTs have a high aspect ratio, the total surface area of working electrodes becomes larger when CNTs are modifi ed on the surface of electrodes.…”
Section: Introductionmentioning
confidence: 99%